1982
DOI: 10.1021/jm00350a008
|View full text |Cite
|
Sign up to set email alerts
|

Monophenolic octahydrobenzo[f]quinolines: central dopamine- and serotonin-receptor stimulating activity

Abstract: Eight monophenolic cis- and trans-4-n-propyl-1,2,3,4,4a,5,6,10b-octahydrobenzo[f]quinolines have been synthesized and tested for central dopamine- and serotonin-receptor stimulating activity, using biochemical and behavioral tests in rats. The trans-7-, -8-, and -9-hydroxy isomers all elicited central pre- and postsynaptic dopaminergic receptor stimulation, while the trans-10-hydroxy isomer was devoid of dopaminergic activity but instead showed central serotoninergic activity. In all four isomeric pairs, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Similar observations have also been made for a series of monophenolic octahydrobenzo[/]quinolines. 24 A monohydroxyl group in the 8-position of the 2-aminotetralin therefore seems to be indispensable for selective 5-HT receptor stimulation. This is also supported by Feenstra et al,25 who found that 21 did not alter the dopamine metabolism (DOPA, HVA, and dopamine levels) in the rat striatum and by the fact that 7,8-dihydroxy-2-(di-n-propylamino) tetralin26 is a DA receptor agonist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have also been made for a series of monophenolic octahydrobenzo[/]quinolines. 24 A monohydroxyl group in the 8-position of the 2-aminotetralin therefore seems to be indispensable for selective 5-HT receptor stimulation. This is also supported by Feenstra et al,25 who found that 21 did not alter the dopamine metabolism (DOPA, HVA, and dopamine levels) in the rat striatum and by the fact that 7,8-dihydroxy-2-(di-n-propylamino) tetralin26 is a DA receptor agonist.…”
Section: Resultsmentioning
confidence: 99%
“…We have earlier pointed out the structural similarities between compound 21, d-LSD, and 5-HT. 24 When the the indole nucleus of 5-HT is superimposed on the indole moiety of d-LSD, the 5-OH group will correspond to the 12-position of d-LSD. Assuming that this is the correct way of comparing 5-HT and d-LSD, it implies that 5-HT has the above-mentioned conformation (see formula of 5-HT) when activating the same 5-HT receptor as d-LSD.…”
Section: Resultsmentioning
confidence: 99%
“…Chroman analogs, such as 5-OH DPAC ( I ] ) , bind with a SAFIR similar to that of the aminotetralins [Cossery et al, 19871. Fused pyran (e.g., CGS 18102 (12); Ki = 9 nM) [Clark et al, 19901 and benzoquinoline (e.g., 13) derivatives of 8-OH DPAT [Wikstrom et al, 1982;Mellin et al, 19911 bind with comparable or a slightly lower affinity. Benzazepine analogs, such as the a,-adrenoceptor antagonist SKF 86466 (14), bind with modest affinity (Ki = 100 nM); Clark and co-workers [ 19901 examined a wide range of such compounds and imply that certain derivatives (Ki = 10-100 nM) may act as 5-HT1, antagonists.…”
Section: Aminotetralinsmentioning
confidence: 99%
“…The key step in this reaction sequence involved the preparation of the tricyclic enamines 10-14 by the procedures of Evans et a1.12 and Kavadias et al 13 The only products isolated in this reaction were the tricyclic enamines 10-14 in which the double bond is in the six-membered ring in conjugation with the benzene ring. If the double bond had been elsewhere, an olefinic proton would have been observed in the 'H NMR spectra.13 The 1,2,4,5-tetrahydro-3H-benz[e]indoles [10][11][12][13][14] were extremely air sensitive oils and could not be distilled. However, these compounds were stable under a nitrogen atmosphere when stored at 0 "C and were used directly in the synthesis of 15-20 without purification.…”
Section: Resultsmentioning
confidence: 99%
“…IR spectra were (t, 3 H, CH,), 1.61 (m, 2 H, CH,CH,), 2.22-3.10 (m, 6 H, ArCH,CH, and NCH,), 3.78 (s, 3 H, OCH,), 5.19 (s, 1 H, ArCH=C) sensitivity. These compounds were used directly in the synthesis of [10][11][12][13][14] (method B). The following compounds were synthesized by method A.…”
Section: Methodsmentioning
confidence: 99%